Tindak Pidana Pencucian Uang Yang Dilakukan Oleh Korporasi: Studi Kasus Putusan Pengadilan Negeri Nomor: 64/Pid.Sus/Tpk/2016/Pn.Bgl - Jessica, Jeanny (UI Scholars Hub, 2021)
The typologies of money laundering are very closely related to corporate activities, which the activities of corporation are involved indirectly or are associated with financial institutions that made corporations very high risk as criminal offender of money laundering crimes. The handling of money laundering cases that corporation as subjects have only been carried out in Bengkulu with the corruption as primary criminal act, whereas will be expected that the application of corporations as subjects of money laundering crimes will also trigger other law enforcement agencies to uncover money laundering cases that made by corporations